2020
DOI: 10.1111/jth.14635
|View full text |Cite
|
Sign up to set email alerts
|

Platelet surface expression of cyclophilin A is associated with increased mortality in patients with symptomatic coronary artery disease

Abstract: Background: Cyclophilin A (CyPA) is an important intracellular molecule mediating essential cellular functions such as signaling and protein folding. Enhanced CyPA platelet surface expression is associated with hypertension and hypercholesterolemia in patients with stable coronary artery disease (CAD). In patients with acute myocardial infarction CyPA platelet surface expression is significantly decreased. The aim of this study was to investigate possible associations of CyPA platelet surface expression and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…This is supported by a study among diabetes patients that demonstrated that rs6850 was associated with increased plasma levels of Cyclophillin A, and an increased likelihood of cardiovascular diseases among patients with or without diabetes [24]. Additionally, Rath et al also reported that rs6850 was associated with recurrent myocardial infarction among patients with symptomatic coronary artery disease [25]. Taken together, these findings could imply that rs6850 increases Cyclophillin A protein expression that affects signaling and protein folding thus promoting susceptibility to various disease pathologies including HIV infectivity and disease progression among non-controllers.…”
Section: Discussionmentioning
confidence: 82%
“…This is supported by a study among diabetes patients that demonstrated that rs6850 was associated with increased plasma levels of Cyclophillin A, and an increased likelihood of cardiovascular diseases among patients with or without diabetes [24]. Additionally, Rath et al also reported that rs6850 was associated with recurrent myocardial infarction among patients with symptomatic coronary artery disease [25]. Taken together, these findings could imply that rs6850 increases Cyclophillin A protein expression that affects signaling and protein folding thus promoting susceptibility to various disease pathologies including HIV infectivity and disease progression among non-controllers.…”
Section: Discussionmentioning
confidence: 82%
“…This is supported by a study among diabetes patients that demonstrated that rs6850 was associated with increased plasma levels of Cyclophillin A, and an increased likelihood of cardiovascular diseases among patients with or without diabetes (24). Additionally, Rath et al (2019) also reported that rs6850 was associated with recurrent myocardial infarction among patients with symptomatic coronary artery disease (25). Taken together, these ndings could imply that rs6850 increases Cyclophillin A protein expression that affects signaling and protein folding thus promoting susceptibility to various disease pathologies including HIV infectivity and disease progression among non-controllers.…”
Section: Discussionmentioning
confidence: 85%
“…CyPA is an intracellular protein that is expressed under inflammatory conditions by several cell types; some of them have been shown to secrete CyPA during in the early stages of pathologies that include atherosclerosis, coronary artery disease (CAD), and acute myocardial infarction [11]. During atherosclerosis, CyPA mediates ox-LDL-induced macrophage activation [12], and it was recently shown that inhibition of CyPA degradation is also prevented by ox-LDL via a mechanism which enlarges early atherosclerotic burden [13].…”
Section: Discussionmentioning
confidence: 99%